Sexual networks of individuals infected with sexually transmitted infections: Structure and disease transmission - Meadows, Emily Christine (University of Ottawa (Canada), 2006)
Increases in the rates of sexually transmitted infections (STIs) suggest that control programs may not be targeting the population responsible for the spread of STIs - core groups. The objective was to examine STI transmission within these groups using both traditional epidemiology and social network analysis. Routine partner notification data, supplemented with more detailed voluntary information, was collected from individuals diagnosed with, or exposed to a STI in Manitoba. Groups of individuals were identified (n=2,508), and their profiles described. Larger groups (size > 15) had more repeat cases, and contacts that were repeatedly named. Three different groups were identified, containing individuals which differed demographically and clinically. This study uniquely identified same-sex partnerships within larger groups. A greater understanding of disease transmission patterns within these groups will clearly aid in the development of targeted education and prevention programs for all STIs.
Keywords: Health Sciences, Epidemiology.